The Effect Of Sukuk On The Profitability Of Islamic Bank In Indonesia - Sholikhin, Mohammad Yusron; Amijaya, Rachmania Nurul Fitri; Herianingrum, Sri (IJIBE (International Journal of Islamic Business Ethics), 2020)
The purpose of this study was to determine the effect of the development of the Sukuk market to the profitability of Islamic banks in Indonesia. This study uses a quantitative method with a vector error correction model. The data used was monthly data Sukuk and profitability of Islamic banks in the years 2011 to 2018. The results of this research are in the long term Sukuk variables have a significant influence on ROA. The results obtained from the t-statistic values of variables Sukuk amounting -6.56088. The value is greater than t table, the Effect of Sukuk itself fairly small to ROA. This study is the first study that examines the influence of Sukuk on the profitability of Islamic banks using a vector error correction model.